The Extended Baryonic Halo of NGC 3923 - Bryan W. Miller; Tomás Ahumada; Thomas H. Puzia; Graeme N. Candlish; Stacy S. McGaugh; J. Christopher Mihos; Robyn E. Sanderson; Mischa Schirmer; Rory Smith; Matthew A. Taylor (Galaxies, 2017)
Galaxy halos and their globular cluster systems build up over time by the accretion of small satellites. We can learn about this process in detail by observing systems with ongoing accretion events and comparing the data with simulations. Elliptical shell galaxies are systems that are thought to be due to ongoing or recent minor mergers. We present preliminary results of an investigation of the baryonic halo—light profile, globular clusters, and shells/streams—of the shell galaxy NGC 3923 from deep Dark Energy Camera (DECam) g and i-band imaging. We present the 2D and radial distributions of the globular cluster candidates out to a projected radius of about 185 kpc, or ∼ 37 R e , making this one of the most extended cluster systems studied. The total number of clusters implies a halo mass of M h ∼ 3 × 10 13 M ⊙ . Previous studies had identified between 22 and 42 shells, making NGC 3923 the system with the largest number of shells. We identify 23 strong shells and 11 that are uncertain. Future work will measure the halo mass and mass profile from the radial distributions of the shell, N-body models, and line-of-sight velocity distribution (LOSVD) measurements of the shells using the Multi Unit Spectroscopic Explorer (MUSE).